Causal relationships between telomere length and liver disease: a Mendelian randomization study - Zhu, Shuangjing; Yang, Mengtao; Wang, Ting; Ding, Zhen (Frontiers in Genetics, 2023)
Background： Leukocyte telomere length and hepatic disorders have been linked in several kinds of research, although their causative association has not been clarified. This study investigated the causative association between the length of telomeres on peripheral blood leukocytes and certain liver disorders.Methods： Mendelian randomization (MR) analysis was used to examine the relationship between leukocyte telomere length and risk of liver disease using the publicly accessible worldwide genewide association study (GWAS) database. The weighted mode, weighted median, and inverse variance weighted (IVW) methods are employed as supplements to the IVW approach, which is the major analytic method.Result： Leukocytes with longer telomeres may have a lower risk of developing cirrhosis (OR=0.645(0.524,0.795), P=3.977E-05) and a higher chance of developing benign liver tumors This is a provisional file, not the final typeset article (OR=3.087(1.721,5.539), P=1.567E-04). There was no direct link between telomere length and fatty liver, liver fibrosis, or liver cancer. Our findings in the replication analysis agreed with theirs.Conclusion： Further research is needed to examine the processes behind the probable causative link between the length of leukocyte telomeres and cirrhosis and benign liver cancers.